Reusable cobalt-phthalocyanine in water: efficient catalytic aerobic oxidative coupling of thiols to construct S–N/S–S bonds. Issue 11 (24th March 2017) - Dou, Yingchao; Huang, Xin; Wang, Hao; Yang, Liting; Li, Heng; Yuan, Bingxin; Yang, Guanyu
Abstract : Reusable Co-catalyzed coupling of thiols to synthesize S–N/S–S bonds in water. Abstract : A new aerobic oxidative coupling of thiols in water to construct sulfenamides or disulfides was developed, utilizing cobalt(ii )phthalocyanine-tetra-sodium sulfonate as the catalyst and O2 as the oxidant. The mother liquor could be recycled up to 20 times with negligible loss of activity and only a minor decrease of product yield.